ANALYZING THE OUTCOMES OF MICROBIOLOGICAL STUDIES RELATED TO VULVAR CANCER (International Conference on Economics, Finance, Banking and Management, 2025)
We conducted a study involving 161 patients with a confirmed diagnosis of cervical cancer who received treatment at the Russian National Medical Research Center. To identify sexually transmitted diseases and opportunistic infections, we utilized cultural or molecular methods, including PCR. Samples were collected from the genitourinary tract, specifically from the endocervix (obtained during a Pap test), as well as urine samples to test for gonorrhea and chlamydial infections